دراسة خواص وتقريب صف التوابع العقدية - علي, محمد (Latakia University Journal -Basic Sciences Series, 2015)
يهدف البحث إلى إدخال صف جديد من التوابع العقدية رمزنا له بالرمز يعتمد في تعريفه على تعريف صف هولدر الشهير ,حيث قمنا بدراسة العلاقة بين الصف الجديد وصف هولدر ومن ثم اثبتنا بعض الخواص التي يتمتع بها الصف . وفي النهاية قمنا بتطبيق هذه الدراسة لتقريب صف التوابع على منحنيات مغلفة تنتمي الى اسرة واسعة من المنحنيات . This research aimed to define a new class of complex functions , which depends in its definition on the definition of famous Holder class. We studied the relation between the new and Holder classes, then we proved some properties of the class . We finally applied this study to approximate the class of complex functions on closed curves , which belong to a wide class of curves.